Intrapancreatic Accessory Spleen Masquerading as a Pancreatic Mucinous Neoplasm - Poola, Shiva; Laks, Shachar; Kragel, Peter; Regan, Kara (The Surgery Journal, 2020)
Incidentally discovered pancreatic cysts have become more common with increasing use of abdominal cross-sectional imaging. Tools that help us to better risk stratify a pancreatic cyst include advanced imaging techniques, such as pancreatic protocol computed tomography (CT) scan or magnetic resonance imaging (MRI) with cholangiopancreatography. Endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) are invasive measures to better define and sample cysts especially if high-risk features are present. EUS may also yield pancreatic cyst fluid for analysis of carcinoembryonic antigen (CEA) which is elevated in mucinous cysts. This case highlights a rare finding of a mucinous, epidermoid cyst in an intrapancreatic accessory spleen (IPAS) with high-risk features on EUS.
Keywords: pancreatic neoplasm; intrapancreatic accessory spleen; endoscopic ultrasound